Intelligent Electric Vehicle Charging Controller: CCCV Concepts, Challenges, and Future Directions - Tole Sutikno; Tri Wahono; Mohd Hatta Jopri (Journal of Electrical, Electronic, Information, and Communication Technology, 2026)
Electric vehicles (EVs) play an important role in the transition to sustainable energy systems, but their success relies heavily on efficient, safe, and adaptive charging systems. The Constant Current Constant Voltage (CCCV) method has become a key strategy in lithium-ion battery charging due to its ability to maintain voltage stability, prevent overcharging, and extend battery life. This paper is a review article that presents a conceptual analysis of CCCV-based EV charging controller systems without involving experiments or simulations. The study synthesizes the current literature to examine the integration of CCCV with Battery Management Systems (BMS), Solid-State Transformers (SST), artificial intelligence (AI), and intelligent grid infrastructure. The novelty of this paper lies in a holistic approach that links the strategies of charge control, power electronics, energy management, and grid stability areas that are often discussed separately. A structured taxonomy and comparative analysis are presented to identify technical challenges, research gaps, and the direction of development of adaptive and AI-based EV charging systems. This review confirms that CCCV remains the main foundation of EV charging, whose performance can be significantly improved through the integration of smart technology and modern grids.